THE IMPACT OF DYNAMIC PRICING REFLECTING FOREIGN EXCHANGE RATE MOVEMENT - Nor Aripin, Adlan Zaidi (2017)
J-Flex Ltd. is an elastomer provider based in Nottingham United Kingdom and has been around since 1984. The company produce and manufacture elastomer products that involves natural and synthetic rubber for various industries including transportation, healthcare and many more. J-Flex has been serving more than 1300 customers focusing on a business to business (B2B) model with flexible pricing. J-Flex resources to produce their products were acquired from various countries and they trade across more than 50 countries. While their trading’s cost is mainly involving on the existing currency exchange rate reflecting pound sterling, they have been experiencing volatile movements within their revenues and profits. The question is whether a system of prices, rapidly updated to reflect exchange rate movements, would stabilise and improve profitability. The potential upside is the transfer of the impact of exchange rate variability to customers. Their main challenges currently are focusing on their pricing strategy where currently they implement a flexible pricing strategy towards their customers and due to this they have been experiencing constant movement in their price and have impacted their profitable. Their proposal is to investigate the strategic impact towards the switch from fixed pricing to a dynamic pricing which provide positive result to further implement dynamic pricing. An evaluation and analysis on the company’s background, industry as well as the overall study of the dynamic pricing with impact reflecting to exchange rate will be used as a basis in strategic analysis and findings towards conclusions and recommendations. Hence, the analysis concerning dynamic pricing towards exchange rate in British Pound (GBP or £), European Currency (EURO or €) and United Stated Dollar (USD or $) refers to the overall study (“report”) focus mainly for the company’s benefit and growth, suggesting that dynamic pricing strategy would be viable and best for the company to apply in order to sustain and achieve profits. Since J-Flex provides a unique and customizable price by each of their customers as of now with fixed pricing strategy and non-attainable actual data from the firm, the assumptions of this report will be using a more generic approach. Special attention is devoted to three distinct approach. First, to better understand the firm’s business environment correspond to actual structural changes in supply and demand based on overall rubber industry, an evaluation on the firm and the industrial background is conducted. In this regard, it appears that the industry has risen beyond what might be justified by the fundamentals for this sector and prove the demand and supply are growing immensely within the next 10 years. Second, the report examines various elements of dynamic price strategy, in this context looking specifically at relative importance of the exchange rate and dynamic pricing, its movements, the types of dynamic pricing as well as understanding the market that J-Flex is trading in. In this context, special attention is devoted to the exchange rate analysis and movements, factors affecting and influencing currency rate, price elasticity as well as the overall competitor analysis that will justify the overall analysis and impact for J-Flex. Accuracy and transparency is a real challenge for this section in the first instance and is potentially complicated further by allegations of manipulation of data, past research and other elements of the market. Third, the report provides relative impact and recommendations for J-Flex to consider with steps to implement the dynamic pricing strategy on a generic level. This is supported with the past research conducted and the recommendation that will help J-Flex to sustain and attain growth through the implementation of dynamic pricing strategy.